Acquisition of industrial enterprises and its relations with regional identity: The case of the beer industry in Central Europe. Issue 4 (8th August 2019) - Materna, Kryštof; Hasman, Jiří; Hána, David
ABSTRACT: The development of globalisation has ushered in fundamental changes that have led to a break in the relationship between places of production and places of consumption, and sometimes a rejection of global products and corporations at the local level in accordance with neolocalism. The objective of the article is to examine the effect of regional identity on the local impacts of global processes by applying a multilevel analysis of the brewing industry, in which consumers are very sensitive to changes in the beer offered and can influence it, for example by putting pressure on representatives of restaurants. Beginning with extensive research on the international level, the authors point out the various impacts of brewery acquisitions in three Central European countries – Czechia, Poland and Slovakia – that differ regarding the role of beer in the identity of their inhabitants. Thereafter, they focus on two Czech beer brands, the production of which was relocated to other regions after acquisitions. Based on field studies in the regions of the brands' original production, the authors find that both brands lost popularity among their original customers. They conclude that for Czech customers, the place of production may be an important factor when choosing a beer brand.